A Genome‐Wide Association Study of Childhood Body Fatness. Issue 2 (24th January 2021) - Warner, Erica T.; Jiang, Lai; Adjei, David Nana; Turman, Constance; Gordon, William; Wang, Lu; Tamimi, Rulla; Kraft, Peter; Lindström, Sara
Abstract : Objective: This study aimed to uncover genetic contributors to adiposity in early life. Methods: A genome‐wide association study of childhood body fatness in 34, 401 individuals within the Nurses' Health Studies and the Health Professionals Follow‐up Study was conducted. Data were imputed to the 1000 Genomes Phase 3 version 5 reference panel. Results: A total of 1, 354 single‐nucleotide polymorphisms ( P < 10 −4 ) were selected for replication in a previously published genome‐wide association study of childhood BMI. Nineteen significant genome‐wide ( P < 5 × 10 −8 ) regions were observed, fourteen of which were previously associated with childhood obesity and five were novel: BNDF ( P = 7.58 × 10 −13 ), PRKD1 ( P = 1.43 × 10 −10 ), 20p13 ( P = 2.05 × 10 −10 ), FHIT ( P = 1.77 × 10 −8 ), and LOC101927575 ( P = 3.22 × 10 −8 ). The BNDF, FHIT, and PRKD1 regions were previously associated with adult BMI. LOC101927575 and 20p13 regions have not previously been associated with adiposity phenotypes. In a transcriptome‐wide analysis, associations for POMC at 2p23.3 ( P = 3.36 × 10 −6 ) and with TMEM18 at 2p25.3 ( P = 3.53 × 10 −7 ) were observed. Childhood body fatness was genetically correlated with hip ( r g = 0.42, P = 4.44 × 10 −16 ) and waist circumference ( r g = 0.39, P = 5.56 × 10 −16 ), as well as age at menarche ( r g = −0.37, P = 7.96 × 10 −19 ). Conclusions: Additional loci that contribute to childhood adiposity were identified, further explicating its genetic architecture.